A215 QUALITY INDICATORS OF UPPER AND LOWER DIGESTIVE ENDOSCOPY IN CHILDREN: A SYSTEMATIC REVIEW AND META-ANALYSIS - Bicamumpaka Shema, A (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Digestive endoscopy is a useful diagnostic and therapeutic tool for children with intestinal diseases. However, unlike litterature on adult population, little data exist in the pediatric litterature regarding quality indicators in digestive endoscopy. Many adult quality indicators are not applicable to children. AIMS: The aims of review of the literature and meta-analysis were: 1) to synthesize published data on the practice of pediatric digestive endoscopy 2) to identify potential quality indicators specific to children. METHODS: A systematic search of the literature in English and French, from 1980 to 2016, was performed via the EMBASE, Medline and PubMed databases. The data extracted related to indications, bowel preparation, sedation, wait times, completion of the procedure, complications and outcomes (macroscopic and microscopic). RESULTS: Of the 301 articles identified, 23 articles were selected. Among these articles, most used general anesthesia and sedation. The choice mainly depended on the patient’s condition, the endoscopist’s preference or the habits of the team. The quality of bowel preparation was insufficient in 17,3% ± 7,6% of the cases (n = 2 studies). Caecum and ileum intubation rates were respectively 88.7% ± 2.3% and 83.9% ± 0.2% (n = 3 studies). Oesogastroduodenoscopies (OGDs) were macroscopically normal in, 51.8% ± 4.3% of cases (n = 6 studies) and 47,8% ±11,8%, microscopically normal (n = 2 studies). Regarding colosnoscopies, 41,6% ± 1,7% (n = 4 studies) and 40,0% ± 10,0% (n = 2 studies) were respectively macroscopically and microscopically normal. The mean rate of complications was 3.4% ± 1.1% (n = 4 studies) for OGD and 2.5% ± 0.7% (n = 5 studies) for colonoscopies. It was also noted that 74.0% to 99.7% of endoscopies had an appropriate indication (n = 3 studies). CONCLUSIONS: The rate of complications in pediatric digestive endoscopy is similar between studies and most of them are benign complications (eg. desaturations). The outcomes between macroscopic and microscopic analysis were similar and high, suggesting either an inappropriate application of the current indications or a need for revision of these indicators. A success rate of colonoscopy reaching the caecum greater than 80% could be an objective to be achieved. The quality of the bowel preparation and the rate of cancellations are an other important criteria but few studies reported these outcomes. Likewise, there was few studies on wait times and the results were significantly different. FUNDING AGENCIES: None